2022
DOI: 10.1111/myc.13497
|View full text |Cite
|
Sign up to set email alerts
|

Update of the Epidemiology of the Sporotrichosis Epidemic in the state of Rio Grande do Sul, Brazil

Abstract: Background Sporotrichosis is a disease not requiring jurisdictional notification and consequently is underreported in Brazil. Therefore, the epidemiological picture even in hyperendemic states is unknown. Thus, we evaluated the occurrence of sporotrichosis throughout the territory of the southern state of Brazil, Rio Grande do Sul (RS). Methods We update the epidemiological situation of sporotrichosis in the southern region of this state and describe the emergence of this disease in the Metropolitan region. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Brazil is facing the largest reported current zoonotic outbreak of CTS globally (9,11,13,28). CTS is a public health issue exacerbated by insufficient public health activities, such as case surveillance, animal control, and diagnostic capacity, and by lack of disease awareness among health professionals and the general population (9,13,25,29). Our study adds relevant epidemiologic information to promote better understanding of CTS in the state of Paraná, Brazil.…”
Section: Discussionmentioning
confidence: 89%
“…Brazil is facing the largest reported current zoonotic outbreak of CTS globally (9,11,13,28). CTS is a public health issue exacerbated by insufficient public health activities, such as case surveillance, animal control, and diagnostic capacity, and by lack of disease awareness among health professionals and the general population (9,13,25,29). Our study adds relevant epidemiologic information to promote better understanding of CTS in the state of Paraná, Brazil.…”
Section: Discussionmentioning
confidence: 89%
“…Besides Rio de Janeiro, atypical zoonotic sporotrichosis cases were also reported in patients from ten additional Brazilian states. Two of these states (Rio Grande do Sul and São Paulo) are nowadays hyperendemic areas for sporotrichosis, starting with outbreak reports since the 2000s [76,[85][86][87], and in eight other states (Paraná, Distrito Federal, Minas Gerais, Pernambuco, Bahia, Rio Grande do Norte, Paraíba, and Espírito Santo) outbreaks of S. brasiliensis infection have been reported in the last five/ten years [79,[88][89][90][91][92][93].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the in vitro activity of two repurposing drugs, either alone or in association with ITZ, against the pathogenic species S. brasiliensis . These isolates were obtained from clinical cases in the two main sporotrichosis hyperendemic regions in Brazil ( Gremião et al, 2020 ; Munhoz et al, 2022 ; Losada et al, 2023 ; Spruijtenburg et al, 2023 ). Sporotrichosis represents a severe public health problem in Brazil and currently it is emerging as a global concern.…”
Section: Discussionmentioning
confidence: 99%